Access to Information and the Role of Friends Related to Sexual Behavior at Risk of Pregnancy in Deaf Adolescents - Aprianti Aprianti; Kismi Mubarokah; Fitria Dewi Puspita Anggraeni; Izzatul Fikrah (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Background: Deaf teenagers have the same growth phase as teenagers in general, but they have limited access to information and limited communication.Objective: This study aims to determine the factors associated with sexual behavior in deaf adolescents.Methods: This research is a quantitative study with a cross sectional design. The population is junior and senior high school students at SLB N Semarang, the sampling technique is total sampling with the inclusion and exclusion criteria set. The number of samples is 38 respondents. Bivariate analysis using Spearman's rank.Results: The results showed that 32.4% of respondents had been in a relationship, and their sexual behavior was 2.9% of respondents who had attached their genitals to clothes, had touched sensitive body parts, and had kissed on the lips. There is a relationship between the role of friends (p value = 0.018) and access to health information (p value = 0.001) with the sexual behavior of deaf adolescents. There is no relationship between the level of knowledge, attitudes, roles of parents and access to health services with the sexual behavior of deaf adolescents.Conclusion: It is necessary to provide education with media that can be accepted and understood by deaf teenagers in accordance with their limitations.